Thermoanalytical study of the complexes of 4-dimethylaminocynnamylidenepyruvate with manganese (II), cobalt (II), nickel (II), cupper (II), zinc (II) and lead (II), in the solid state - Schnitzler, E.; Lazzarotto, M.; Carvalho, MAD; Ionashiro, Massao [UNESP] (Editora Unesp, 2002)
Solid state compounds M-4-DMCP, where 4-DMCP is 4-dimethylaminocynnamylidenepyruvate and M represents Mn (II), Co (II), Ni (II), Cu (II), Zn (II) and Pb (II) were prepared. These compounds were studied by thermoanalytical techniques: thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometric titration with EDTA. From the results obtained by the complexometric titration with EDTA, TG, DTG and DSC curves, was possible to establish the hydration degree, stoichiometry and thermal stability of the prepared compounds.
Keywords: 4-dimethylaminocynnamylidenepyruvate; thermal analysis; TG; DSC